2019
DOI: 10.1371/journal.pone.0218887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early protein and energy intakes on neurodevelopment at 2 years of corrected age in very low birth weight infants: A single-center observational study

Abstract: Introduction Aggressive nutritional strategy, particularly enhancing early provision of energy and protein, has appeared to reduce postnatal growth failure and improve later developmental outcomes. But the amount of macronutrients required remains unclear. The aim of this study was to investigate the impact of protein and energy intakes during the first two weeks after birth on neurodevelopmental outcomes. Methods This retrospective cohort study of very low birth weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Protein intakes in our study cohort were largely within this range. In contrast to these findings, another report noted that high protein intake (4 g/kg/day) was associated with neurodevelopmental impairments at 2 years in very low birth weight children 38 . These findings suggest that adequate early protein intake is essential for optimal brain growth, although adverse effects of protein overfeeding cannot be excluded.…”
Section: Discussionmentioning
confidence: 79%
“…Protein intakes in our study cohort were largely within this range. In contrast to these findings, another report noted that high protein intake (4 g/kg/day) was associated with neurodevelopmental impairments at 2 years in very low birth weight children 38 . These findings suggest that adequate early protein intake is essential for optimal brain growth, although adverse effects of protein overfeeding cannot be excluded.…”
Section: Discussionmentioning
confidence: 79%
“…In preterm infants, early parenteral protein intake has been associated with lower M-ABC scores [46], higher odds on cerebral palsy [46], and lower cognitive scores [47]. Additionally, increased early total protein intake was associated with higher odds on neurodevelopmental impairments [14]. On the contrary, several studies show positive associations between total protein intake [3,12] or enteral protein intake [46,48,49] and NDO [15].…”
Section: Protein Intake and Neurodevelopmental Outcomementioning
confidence: 99%
“…Despite promising associations between nutrient intake and brain development, nutritional effects on NDO remain inconclusive [3,[11][12][13][14][15]. A meta-analysis revealed that increased early enteral nutrition in preterm infants may support survival without neurodevelopmental impairment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm infants experience high rates of postnatal growth restriction [1], with a particular need for protein supply for growth and improved neurodevelopmental outcomes [2,3]. Human milk (HM) use is very well tolerated and is acknowledged as ideal nutritional support for improving the survival and long-term outcomes of neonates [4].…”
Section: Introductionmentioning
confidence: 99%